Solusi Melawan Rasa Kecemasan Dalam Al- Quran Terhadap Kehidupan “Kajian Al Huzn dan Al Khauf”: Quranic Solutions to Overcome Life Anxiety: A Study of Al-Huzn and Al-Khauf - Prayoga, Raditya (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Anxiety is a significant psychological issue in the dynamics of human life, particularly during the emerging adulthood phase, which is vulnerable to quarter-life crises. This study aims to explore Quranic solutions for overcoming anxiety through a thematic study of the concepts of al-huzn (sadness) and al-khauf (fear). The method employed is descriptive qualitative with a content analysis approach to Quranic verses and scholars' interpretations, including the Sufistic perspective of Imam Al-Qushayri. The results indicate that the Quran views anxiety as part of human nature (fitrah) rooted in human cognitive limitations regarding the future and potential spiritual emptiness. The curative solutions offered by the Quran include moral reconstruction (akhlak), the implementation of patience (sabr) as a form of active resilience, and the establishment of prayer (salah) as a means of spiritual catharsis. A key finding in this study confirms that achieving ma'rifatullah (gnosis/knowledge of Allah) is the primary instrument in transforming destructive fear into tranquility of the soul (tuma'ninah). This study concludes that the integration of Quranic psycho-spiritual values can serve as a solution-oriented argumentative basis for individuals in facing the complexities of modern challenges.